Rubber composition
A rubber composition with optimized sulfur and accelerator ratios in highly saturated diene elastomers addresses slow curing and cohesive strength issues, enhancing tire durability and productivity.
Patent Information
- Application Number
- JP2021513298
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-09-11
- Filing Date
- 2019-09-11
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2039-09-11
AI Technical Summary
Highly saturated diene elastomers cure slowly, leading to longer press residence times and increased bubble formation, which affects tire durability and productivity, while requiring improved cohesive strength for heavy loads.
A rubber composition using a highly saturated diene elastomer with specific ratios of sulfur, a mixture of primary and secondary accelerators, and carbon black, optimized for faster curing and enhanced cohesive properties.
The composition achieves a balance between cohesive strength and press cure time, reducing bubble formation and improving tire durability, especially for heavy loads.
Smart Images

Figure 0007616990000001 
Figure 0007616990000002 
Figure 0007616990000003
Abstract
Description
[Technical field]
[0001] The field of the invention is that of rubber compositions based on highly saturated diene elastomers intended to be used in tires, and in particular in their treads. [Background technology]
[0002] For the same elastomer, the level of stiffness of the rubber composition depends on the degree of vulcanization of the elastomer, which depends on both the vulcanization reaction rate and the residence time of the rubber composition in the curing press. It is known that the rubber composition continues to harden even after it is removed from the curing press. The duration of the hardening outside the press is longer when the rubber composition is in the form of a large object. If the rubber composition is not fully hardened when it leaves the press, the viscosity of the rubber composition may cause bubbles to form in the rubber composition as the hardening continues outside the press. The formation of bubbles in the rubber composition is a defect in the uniformity of the rubber composition, which may reduce the durability of the tire containing the rubber composition. Therefore, it is desirable that the rubber composition has sufficient stiffness at the end of the hardening in the press to prevent the formation of bubbles.
[0003] Highly saturated diene elastomers containing at least 50 mol % of ethylene units have the drawback of vulcanizing with a slower reaction rate than highly unsaturated diene elastomers containing more than 50 mol % of diene units. Therefore, a longer residence time in the curing press is required to vulcanize a rubber composition containing a highly saturated diene elastomer, especially when it is desired to avoid the aforementioned bubble phenomenon. The lower reactivity of highly saturated diene elastomers with respect to vulcanization is therefore reflected by a longer occupancy time of the press by the rubber composition and therefore a longer production cycle, which has the effect of reducing the productivity of tire manufacturing plants.
[0004] Moreover, it is also important to provide a rubber composition with good cohesion, since, for example, during rolling, the tread is exposed to mechanical stresses and stress factors resulting from direct contact with the ground. As a result, crack initiation sites are formed, which during their propagation on the surface or within the tread can destroy the material that constitutes the tread. This tread damage reduces the useful life of the tire tread. Good cohesion is particularly sought for tires mounted on vehicles that transport heavy loads, since the mechanical stresses and stress factors experienced by the tire are amplified under the effect of the weight carried by the tire.
[0005] It remains a problem to obtain rubber compositions having an improved compromise between cohesive properties and press cure times. Summary of the Invention [Problem to be solved by the invention]
[0006] The applicant has discovered a rubber composition that can address this problem. [Means for solving the problem]
[0007] A first subject of the present invention is therefore a rubber composition based on at least a highly saturated diene elastomer, comprising carbon black and a vulcanization system comprising sulfur and a vulcanization accelerator, the highly saturated diene elastomer is a copolymer of ethylene and a 1,3-diene, the ethylene units representing at least 50 mol % of the monomer units of the copolymer; - the content of highly saturated diene elastomer in the rubber composition is at least 50 phr; - the vulcanization accelerator is a mixture of a primary accelerator and a secondary accelerator, - the mass ratio between the amount of the secondary accelerator and the total amount of accelerators is less than 0.7, the total amount of accelerators being the sum of the mass of the primary accelerator and the mass of the secondary accelerator in the rubber composition; - Mass ratios are calculated from quantities expressed in phr It is a rubber composition.
[0008] Another subject of the invention is a tire comprising a rubber composition according to the invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] I. Detailed Description of the Invention Any interval of values indicated by the expression "between a and b" denotes a range of values greater than "a" and less than "b" (i.e. excluding the extreme values a and b), whereas any interval of values indicated by the expression "a to b" means a range of values extending from "a" to "b" (i.e. including the precise extreme values a and b). The abbreviation "phr" means parts by weight per 100 parts of elastomer (rubber) (or the sum of the elastomers, if several elastomers are present).
[0010] In this patent application, the mass ratios between the various components of the rubber composition are calculated from the contents or amounts of the components expressed in phr.
[0011] In the present description, the expression "composition based on" should be understood to mean a composition comprising a mixture and / or a product of an in situ reaction of the various components used, some of these base components (for example elastomers, fillers or components of the vulcanization system or other additives conventionally used in rubber compositions intended for the manufacture of tires) that are prone to or are intended to react with one another at least in part during the various stages of the manufacture of the composition intended for the manufacture of tires.
[0012] In this patent application, the expression "all monomeric units of an elastomer" or "total amount of monomeric units of an elastomer" means all the constituent repeating units of an elastomer obtained by the insertion of monomers into the elastomer chain by polymerization. Unless otherwise indicated, the content of monomeric or repeating units in highly saturated diene elastomers is expressed as a mole percentage calculated based on all monomeric units of the elastomer.
[0013] The compounds mentioned in the description may be of fossil or bio-based origin. In the latter case, they may be derived partially or completely from biomass or may be obtained from renewable starting materials derived from biomass. Elastomers, plasticizers, fillers, etc. are of particular concern.
[0014] Elastomers useful for the purposes of the present invention are highly saturated diene elastomers, preferably statistical, containing ethylene units obtained by polymerization of ethylene. In one well-known manner, the term "ethylene units" means -(CH2-CH2)- units obtained by insertion of ethylene into the elastomer chain. Highly saturated diene elastomers are rich in ethylene units, since they make up at least 50 mol% of all monomer units of the elastomer.
[0015] Preferably, the highly saturated diene elastomer comprises at least 65 mol% of ethylene units, in other words, the ethylene units are preferentially at least 65 mol% of all monomer units of the highly saturated diene elastomer, and more preferentially, the highly saturated diene elastomer comprises between 65 mol% and 90 mol% of ethylene units, the molar percentages being calculated based on all monomer units of the highly saturated diene elastomer.
[0016] Since the highly saturated diene elastomer is a copolymer of ethylene and 1,3-diene, it also includes 1,3-diene units resulting from the polymerization of 1,3-dienes. In one known manner, the term "1,3-diene units" means units resulting from the insertion of 1,3-dienes by 1,4-addition, 1,2-addition, or, in the case of isoprene, 3,4-addition. 1,3-diene units are, for example, units of 1,3-dienes containing 4 to 12 carbon atoms, such as 1,3-butadiene, isoprene, 1,3-pentadiene, or aryl-1,3-butadiene. Preferably, the 1,3-diene is 1,3-butadiene, in which case the highly saturated diene elastomer is a copolymer of ethylene and 1,3-butadiene, which is preferably statistical.
[0017] The highly saturated diene elastomer useful for the purposes of the present invention can be obtained by various synthesis methods known to those skilled in the art, depending in particular on the target microstructure of the highly saturated diene elastomer.In general, it can be prepared by copolymerization of at least 1,3-dienes, preferably 1,3-butadiene, with ethylene, in the presence of a catalytic system, in particular comprising a metallocene complex, by known synthesis methods.In this respect, mention may be made of catalytic systems based on metallocene complexes, which are described in the applicant's EP 1092731, WO 2004 / 035639, WO 2007 / 054223 and WO 2007 / 054224. Highly saturated, even statistically saturated, diene elastomers can also be prepared by methods using preformed catalyst systems such as those described in WO 2017 / 093654 A1, WO 2018 / 020122 A1, and WO 2018 / 020123 A1.
[0018] The highly saturated diene elastomer in the rubber composition defined in any one of claims 1 to 14 preferably contains units of the formula (I) or units of the formula (II). [ka] -CH2-CH(CH=CH2)- (II)
[0019] The presence of the saturated 6-membered ring unit 1,2-cyclohexanediyl of formula (I) in the copolymer can be obtained by a very specific sequence of insertions of ethylene and 1,3-butadiene in the growing polymer chain. When the highly saturated diene elastomer comprises units of formula (I) or units of formula (II), the molar percentages o and p of the units of formula (I) and of the units of formula (II), respectively, in the highly saturated diene elastomer preferably satisfy the following formula (eq.1), more preferentially formula (eq.2), where o and p are calculated based on all the monomer units of the highly saturated diene elastomer. 0 <o+p≦25 (eq.1) 0 <o+p<20 (eq.2)
[0020] The highly saturated diene elastomers useful for the purposes of the present invention may consist of a mixture of highly saturated diene elastomers differing from one another in their microstructure or macrostructure.
[0021] According to the invention, the content of highly saturated diene elastomer in the rubber composition is at least 50 parts by weight per 100 parts of elastomer (rubber) of the rubber composition (phr). Preferably, the content of highly saturated diene elastomer in the rubber composition varies within a range ranging from 80 to 100 phr. More preferentially, it varies within a range ranging from 90 to 100 phr.
[0022] A vulcanization system useful for the purposes of the present invention is essentially characterized by comprising sulphur and a vulcanization accelerator. By definition, the sulphur content and the content of vulcanization accelerator in the vulcanization system are both strictly greater than 0 phr. Advantageously, the sulphur content in a rubber composition as defined in any one of claims 1 to 15 is greater than 0.3 phr. Advantageously, the amount of vulcanization accelerator, i.e. the sum of the amount of primary accelerator and the amount of secondary accelerator, in a rubber composition as defined in any one of claims 1 to 15 is at least 0.5 phr.
[0023] The sulfur is typically provided in the form of molecular sulfur or sulfur donors, preferably in molecular form. Sulfur in molecular form is also referred to as molecular sulfur. The term "sulfur donor" means any compound that releases sulfur atoms, optionally bonded in the form of polysulfide chains, that can be inserted into the polysulfide chains formed during vulcanization and crosslinking of the elastomer chains. The sulfur content in the rubber composition is preferentially less than 1 phr, preferably between 0.3 and 1 phr.
[0024] According to a more preferred embodiment of the invention, the sulfur content in the rubber composition is less than 0.95 phr, preferably between 0.3 phr and 0.95 phr.
[0025] According to an even more preferred embodiment of the invention, the sulphur content in the rubber composition is less than 0.8 phr, preferably between 0.3 phr and 0.8 phr.
[0026] The vulcanization accelerator is a mixture of primary and secondary accelerators, and the term "primary accelerator" means one primary accelerator or a mixture of several primary accelerators. Similarly, the term "secondary accelerator" means one secondary accelerator or a mixture of several secondary accelerators. Thus, the primary accelerator (whether in the form of a mixture or not) and the secondary accelerator (whether in the form of a mixture or not) are the only accelerators of the rubber composition. According to the regulations, the content of both the primary accelerator and the secondary accelerator in the vulcanization system is strictly more than 0 phr.
[0027] As (primary or secondary) vulcanization accelerators, any compound capable of functioning as an accelerator of the vulcanization of diene elastomers in the presence of sulfur can be used, in particular accelerators of the thiazole type and their derivatives, accelerators of the sulfenamide type for the primary accelerators, or accelerators of the thiuram, dithiocarbamate, dithiophosphate, thiourea and xanthate type for the secondary accelerators.
[0028] Examples of primary accelerators include, inter alia, sulfenamide compounds such as N-cyclohexyl-2-benzothiazylsulfenamide ("CBS"), N,N-dicyclohexyl-2-benzothiazylsulfenamide ("DCBS"), N-tert-butyl-2-benzothiazylsulfenamide ("TBBS"), and mixtures of these compounds. The primary accelerator is preferentially a sulfenamide, more preferentially N-cyclohexyl-2-benzothiazylsulfenamide.
[0029] Examples of secondary accelerators include, inter alia, thiuram disulfides, such as tetraethyl thiuram disulfide, tetrabutyl thiuram disulfide ("TBTD"), tetrabenzyl thiuram disulfide ("TBZTD"), and mixtures of these compounds. The secondary accelerator is preferentially a thiuram disulfide, more preferentially tetrabenzyl thiuram disulfide.
[0030] Preferably, the vulcanization accelerator is a mixture of sulfenamide and thiuram disulfide, advantageously, the vulcanization accelerator is a mixture of N-cyclohexyl-2-benzothiazyl sulfenamide and thiuram disulfide, more advantageously, the vulcanization accelerator is a mixture of N-cyclohexyl-2-benzothiazyl sulfenamide and tetrabenzyl thiuram disulfide.
[0031] According to the invention, the mass ratio between the amount of the secondary accelerator and the total amount of accelerators is less than 0.7, the total amount of accelerators being the sum of the mass of the primary accelerator and the mass of the secondary accelerator in the rubber composition. In other words, the mass content or mass of the secondary accelerator is less than 70% by mass of the total amount of accelerators. Preferably, the mass ratio between the amount of the secondary accelerator and the total amount of accelerators is greater than 0.05, in particular between 0.05 and 0.7.
[0032] Preferably, the mass ratio between the amount of secondary accelerator and the total amount of accelerator is preferentially less than 0.5, and even more preferentially less than or equal to 0.3. These preferential ranges allow a further optimization of the compromise between cohesive properties and press cure time, by significantly reducing the press processing time, even in the presence of crack initiation sites in the rubber composition, while at the same time maintaining good restraint properties.
[0033] According to a preferential embodiment, the mass ratio between the sulfur content in the rubber composition and the total amount of accelerators is less than 1, preferably less than or equal to 0.7 and more preferentially less than 0.6. The use of such a ratio makes it possible to obtain a composition with further improved cohesive properties.
[0034] According to a particularly preferred embodiment of the invention, the sulfur content in the rubber composition is less than 1 phr and the mass ratio between the sulfur content and the total amount of accelerators in the rubber composition is less than 1. This double condition regarding the sulfur content and the mass ratio between the sulfur content and the total amount of accelerators makes it possible to obtain even higher cohesion. The cohesion properties are further improved if the sulfur content is low and the mass ratio between the sulfur content and the total amount of accelerators is low, in particular if the sulfur content is within the preferential ranges according to claims 7 and 8 and the mass ratio between the sulfur content and the total amount of accelerators is within the preferential ranges according to claim 10.
[0035] In one well-known approach, the vulcanization system may also include a vulcanization activator, for example a metal oxide such as zinc oxide, or a fatty acid such as stearic acid.
[0036] According to the invention, the rubber composition comprises carbon black as reinforcing filler, which typically consists of nanoparticles having a mean (mass-average) size of less than 1 micrometer, generally less than 500 nm, usually between 20 and 200 nm, particularly and more preferentially between 20 and 150 nm.
[0037] Any carbon black is suitable for use as carbon black, in particular the blacks conventionally used in tires or their treads (known as tire grade blacks). Among the latter, mention may be made in particular of the reinforcing carbon blacks of the 100, 200 and 300 series, or of the 500, 600 or 700 series (ASTM grades), such as blacks of N115, N134, N234, N326, N330, N339, N347, N375, N550, N683 and N772. When the rubber composition according to the invention is used in the tread, the carbon black is preferentially a 100 or 200 series carbon black.
[0038] The carbon black content can vary within wide limits and can be adjusted by the skilled person depending on the intended use of the rubber composition, especially in the tire sector. For the use of the rubber composition in treads for vehicles intended to transport heavy loads, the carbon black content in the rubber composition is preferentially between 25 phr and 65 phr. For such use in the heavy goods vehicle sector, the rubber composition may have an insufficient reinforcement level below 25 phr and may show excessive hysteresis above 65 phr.
[0039] The rubber compositions useful for the purposes of the present invention may also contain all or some of the usual additives conventionally used in elastomeric compositions intended for use in tires, such as tire treads, such as, for example, fillers, such as silica, alumina, processing agents, plasticizers, pigments, protective agents, such as anti-ozone waxes, chemical antioxidants, and antioxidants.
[0040] The rubber composition can be produced in a suitable mixer using two successive stages of preparation according to general procedures well known to those skilled in the art: a first stage (sometimes called the "non-productive" stage) of thermomechanical working or kneading at high temperatures up to a maximum temperature between 110°C and 190°C, preferably between 130°C and 180°C, followed by a second stage (sometimes called the "productive" stage) of mechanical working at a lower temperature, typically below 110°C, for example between 40°C and 100°C, during which last stage the sulfur or sulfur donors and vulcanization accelerators are mixed in.
[0041] By way of example, the first stage (non-productive) is carried out as one thermomechanical step, during which all the necessary ingredients, except for the sulfur and the vulcanization accelerator, optional additional processing agents and various other additives are introduced into a suitable mixer, such as a conventional internal mixer. The total mixing time during this non-productive stage is preferably between 1 and 15 minutes. After cooling the mixture thus obtained during the first non-productive stage, the sulfur and the vulcanization accelerator are then added at low temperature, generally in an external mixer, such as an open mill; the whole is mixed for a few minutes, for example between 2 and 15 minutes (productive stage).
[0042] The rubber composition is calendered or extruded to preferably form all or part of the tread profile of a tire.
[0043] Another subject of the present invention is a tire comprising a rubber composition according to the invention, which preferably comprises the rubber composition in its tread, in particular the part of its tread intended to come into contact with the rolling ground, which consists entirely or partly of the rubber composition according to the invention. The tire may be in the raw form (i.e. before the step of curing the tire) or in the form to be cured (i.e. after the step of curing the tire). The tire is preferentially a tire for vehicles intended for the transportation of heavy loads, such as heavy goods vehicles and earthmoving vehicles.
[0044] The above mentioned characteristics of the invention, and others, will be more clearly understood on reading the following description of some embodiments of the invention, given by way of non-limiting example. EXAMPLES
[0045] II. Examples of the Invention II.1 Tests and measurements: II.1-1 Determination of the microstructure of elastomers: Determining the microstructure of elastomers 1 H NMR analysis, 1 When the resolution of H NMR analysis is not sufficient to assign and quantify all species, 13 C NMR analysis is performed in combination with a Bruker 500 MHz NMR spectrometer at frequencies of 500.43 MHz for proton measurements and 125.83 MHz for carbon measurements.
[0046] For insoluble elastomers that swell in solvents, a 4 mm z-grad HRMAS probe is used for proton and carbon measurements in proton decoupled mode. Spectra are acquired at spinning speeds of 4000 Hz to 5000 Hz.
[0047] For measurements on soluble elastomers, a liquid NMR probe is used to measure protons and carbons in proton-coupled mode.
[0048] The preparation of the insoluble sample is carried out in a rotor filled with the material to be analyzed and a swellable deuterated solvent, typically deuterated chloroform (CDCl3). The solvent used must always be deuterated and its chemistry can be adapted by the skilled artisan. The amount of material used is adjusted to obtain a spectrum of sufficient sensitivity and resolution.
[0049] Soluble samples are dissolved in a deuterated solvent (approximately 25 mg of elastomer in 1 mL), typically deuterated chloroform (CDCl3). The solvent or solvent blend used must always be deuterated, and its chemistry can be adapted by one skilled in the art.
[0050] In both cases (soluble or swollen samples): A 30° single pulse sequence is used for proton NMR. The spectral window is set so that all resonance lines belonging to the molecule being analyzed are measured. The number of accumulations is set to provide a signal-to-noise ratio sufficient for quantification of each unit. The recycle delay between each pulse is adapted so that quantitative measurements are made.
[0051] A 30° single pulse sequence is used for carbon NMR, and proton decoupling is performed only during acquisition to avoid the Nuclear Overhauser Effect (NOE) and maintain quantitation. The spectral window is set so that all resonance lines belonging to the molecule being analyzed are measured. The number of accumulations is set to provide a signal-to-noise ratio sufficient for quantitation of each unit. The recycle delay between each pulse is adapted so that quantitative measurements are made.
[0052] NMR measurements are carried out at 25°C.
[0053] II.1-2 Mechanical strength in the presence of crack initiation sites (tearability): The tear strength and deformation of the test specimens are measured, which are stretched at 500 mm / min to break them. The tensile test specimens consist of parallelepiped-shaped rubber slabs, for example with a thickness between 1 and 2 mm, a length between 130 and 170 mm, and a width between 10 and 15 mm, each of the two side ends being covered in the longitudinal direction with a cylindrical rubber bead (diameter 5 mm) for fixing in the jaws of a tensile tester. Before the start of the test, three very fine notches between 15 and 20 mm in length are made with a razor blade, one at each end of the specimen and one in the center, aligned at the mid-length in the longitudinal direction of the specimen. The force acting to break (N / mm) is determined and the elongation at break is measured. The test was carried out in air at a temperature of 100°C. A high value reflects good cohesion of the rubber composition, even with crack initiation sites.
[0054] II.1-3 Tensile test: The tests for elongation at break (EB%) and stress at break (BS) are based on standard NF ISO 37 of December 2005 on H2 dumbbell specimens and are measured at a traction speed of 500 mm / min. The elongation at break is expressed as a percentage of the elongation. The stress at break is expressed in MPa. All tensile test measurements are performed at 60°C.
[0055] II.1-4 Curing properties: The measurements are carried out at 150 °C with an oscillating chamber rheometer according to standard DIN 53529-Part 3 (June 1983). The change in the rheometer torque as a function of time indicates the change in hardening of the composition as a result of the vulcanization reaction. The measured values are processed according to standard DIN 53529-Part 2 (March 1983). Ti is the induction period, i.e. the time required for the start of the vulcanization reaction. T95 is the time required to reach 95% conversion, i.e. 95% of the difference between the minimum and maximum torque. K (min -1 The first-order conversion rate constant, expressed in units of , has also been measured, which allows evaluation of the vulcanization reaction rate.
[0056] II.2 Preparation of the rubber composition: Rubber compositions, the formulation details of which are shown in Table 1, were prepared in the following manner: The elastomer, the reinforcing filler and the various other ingredients, except for the sulfur and the vulcanization accelerator, are successively introduced into the internal mixer (final degree of filling: about 70% by volume), the initial container temperature being about 80° C. Then, the thermomechanical work (non-productive phase) is carried out in one step, lasting a total of about 3-4 minutes, until a maximum "drop-off" temperature of 165° C. is reached. The mixture thus obtained is recovered, cooled, and then the sulfur and the vulcanization accelerator are mixed in on the mixer (homofinisher) at 30° C., and the whole is kneaded for a suitable time (for example about 10 minutes) (productive phase).
[0057] The compositions thus obtained are subsequently calendered into either slabs (2-3 mm thick) or thin rubber sheets for the measurement of their physical or mechanical properties, or extruded into the form of tire treads.
[0058] The elastomer (EBR) is prepared by the following procedure: 30 mg of the metallocene [{Me2SiFlu2Nd(μ-BH4)2Li(THF)}2, symbol Flu is the compound of formula C 13 H8] is introduced into a Steinie in a first glove box. The cocatalyst butyloctylmagnesium, previously dissolved in 300 ml of methylcyclohexane in a second Steinie bottle, is introduced into the first Steinie bottle containing the metallocene in a ratio of 0.00007 mol / L metallocene, 0.0004 mol / L cocatalyst. After 10 minutes of contact at room temperature, a catalyst solution is obtained. This catalyst solution is then introduced into the polymerization reactor. The temperature in the reactor is then raised to 80° C. After reaching this temperature, the reaction is started by injecting a gaseous mixture of ethylene and 1,3-butadiene (80 / 20 mol%) into the reactor. The polymerization reaction is allowed to proceed at a pressure of 8 bar. The ratios of metallocene and cocatalyst are 0.00007 mol / L and 0.0004 mol / L, respectively. The polymerization reaction is stopped by cooling, degassing the reactor and adding ethanol. An antioxidant is added to the polymer solution. The copolymer is recovered by drying in a vacuum oven.
[0059] Rubber compositions C5 to C11 are according to the invention. Rubber compositions C12 and C13 are not according to the invention and have a ratio between the mass of the secondary accelerator and the sum of the mass of the primary accelerator and the mass of the secondary accelerator of 0.7 or more. Compositions C1 to C4 which do not contain any secondary accelerator are not according to the invention.
[0060] II.3 Results: The results are shown in Table 2.
[0061] The results show that rubber compositions C5 to C11 are the ones that exhibit the best compromise between cohesive properties and press cure time. Among these compositions according to the invention, compositions C5 to C10 turn out to be the most advantageous in terms of both cohesive properties and press cure time. Composition C13, which is not according to the invention, in which a secondary accelerator is the only accelerator in the rubber composition, is able to reduce the press cure time, but this result is obtained at the expense of cohesive properties. Composition C12, which is not according to the invention, in which more than 70% by weight of the accelerator a secondary accelerator is used, is also able to reduce the press cure time, but this result is also obtained at the expense of cohesive properties.
[0062] As regards compositions C1 to C4, which are not according to the invention, they have these good cohesive properties, but these results are obtained at the expense of the curing properties with respect to productivity, since the press curing times are much longer.
[0063] [Table 1]
[0064] [Table 2]
Claims
1. A rubber composition based on at least a highly saturated diene elastomer, carbon black, and a vulcanization system containing sulfur and a vulcanization accelerator, the highly saturated diene elastomer is a copolymer of ethylene and a 1,3-diene, the ethylene units representing at least 50 mol % of the monomer units of the copolymer; the content of highly saturated diene elastomer in the rubber composition is at least 50 phr, the vulcanization accelerator is a mixture of a primary accelerator and a secondary accelerator, the mass ratio between the amount of secondary accelerator and the total amount of accelerator is less than 0.5, said total amount of accelerator being the sum of the mass of primary accelerator and the mass of secondary accelerator in said rubber composition; said mass ratios are calculated from amounts expressed in phr, the primary accelerator is a sulfenamide and the secondary accelerator is a thiuram disulfide; the sulfur content is less than 1 phr; The rubber composition.
2. The rubber composition of claim 1, wherein said primary accelerator is N-cyclohexyl-2-benzothiazylsulfenamide.
3. 3. The rubber composition of claim 1 or 2, wherein the secondary accelerator is tetrabenzyl thiuram disulfide.
4. 4. The rubber composition according to claim 1, wherein the mass ratio between the sulfur content and the total amount of accelerators is less than 1, said mass ratio being calculated from the content and the amount expressed in phr.
5. The rubber composition according to any one of claims 1 to 4, wherein the 1,3-diene is 1,3-butadiene.
6. The rubber composition according to any one of claims 1 to 5, wherein the content of said highly saturated diene elastomer in said rubber composition varies within a range ranging from 80 to 100 phr.
7. The rubber composition according to any one of claims 1 to 6, wherein the carbon black content is between 25 phr and 65 phr.
8. A tire comprising the rubber composition according to any one of claims 1 to 7.
Citation Information
Patent Citations
Rubber composition containing a highly saturated diene elastomer
JP2016505697A
Rubber composition and method for producing the same, and method of evaluating wear resistance of rubber composition
JP2018028014A
Rubber blend and tire with tread thereof
US5087668A
Anti-vibration rubber composition, crosslinked Anti-vibration rubber composition, and Anti-vibration rubber
WO2013114877A1
Rubber composition for tires, and pneumatic tire using same
WO2014129662A1